Modernism and race - Platt, Len (Cambridge University Press, 2011)
"The 'transnational' turn has transformed modernist studies, challenging Western authority over modernism and positioning race and racial theories at the very centre of how we now understand modern literature. Modernism and Race examines relationships between racial typologies and literature in the late nineteenth and early twentieth centuries, drawing on fin de sie;cle versions of anthropology, sociology, political science, linguistics and biology. Collectively, these essays interrogate the anxieties and desires that are expressed in, or projected onto, racialized figures. They include new outlines of how the critical field has developed, revaluations of canonical modernist figures like James Joyce, T.S. Eliot, Ford Madox Ford and Wyndham Lewis, and accounts of writers often positioned at the margins of modernism, such as Zora Neale Hurston, Claude McKay and the Holocaust writers Solomon Perel and Gisella Perl. This timely collection by leading scholars of modernism will make an important contribution to a growing field"--